2009
DOI: 10.1063/1.3267862
|View full text |Cite
|
Sign up to set email alerts
|

Conical Intersections, charge localization, and photoisomerization pathway selection in a minimal model of a degenerate monomethine dye

Abstract: We propose a minimal model Hamiltonian for the electronic structure of a monomethine dye, in order to describe the photoisomerization of such dyes. The model describes interactions between three diabatic electronic states, each of which can be associated with a valence bond structure. Monomethine dyes are characterized by a charge-transfer resonance; the indeterminacy of the single-double bonding structure dictated by the resonance is reflected in a duality of photoisomerization pathways corresponding to the d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 95 publications
1
38
0
Order By: Relevance
“…The fact that SA3-CAS(4,3) solutions with the same structure can be found for these distinct molecules suggests that the solutions are stable, and that they are a general feature of dyes from this class. 45,47,48 Benchmark studies 49,50 have shown that the excitation energies of anionic GFP chromophore models calculated with multireference perturbation theory and SA-CASSCF models are not sensitive to basis set or active space size within a range of 0.2 eV, which is within quoted reliability limits 43,51,52 of such models. The systems studied here should be easier to deal with than this, because they are all cations.…”
Section: A Computationsmentioning
confidence: 76%
“…The fact that SA3-CAS(4,3) solutions with the same structure can be found for these distinct molecules suggests that the solutions are stable, and that they are a general feature of dyes from this class. 45,47,48 Benchmark studies 49,50 have shown that the excitation energies of anionic GFP chromophore models calculated with multireference perturbation theory and SA-CASSCF models are not sensitive to basis set or active space size within a range of 0.2 eV, which is within quoted reliability limits 43,51,52 of such models. The systems studied here should be easier to deal with than this, because they are all cations.…”
Section: A Computationsmentioning
confidence: 76%
“…This is also true in non-symmetric methines with very small diabatic gap 37 . The reason why our model predicts a symmetric twist distribution can be traced to the neglect of other intramolecular displacements that could break symmetry in the any real specific case.…”
Section: Discussionmentioning
confidence: 73%
“…In particular, these geometries are accessible from FC in gas phase. This is contraindicated by ab initio calculations on monomethine cyanines 35 , as well as non-symmetric monomethines with small diabatic gap 37 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations